PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA PENGRAJIN SENTRA INDUSTRI KECIL TENUN IKAT - Sonang Sitohang (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
This study aimed is to analyze both simultaneously and partially the effect of the variable quality of human resources consisting of; technical skill, mental attitude, work discipline, work motivation, as well as between the four variables which are the dominant influence on the performance weaving ikad craftsmen small industries. Sampling technique use the census method. The number of respondents who were 52 of weaving craftsmen small industries in Lamongan. Instrument tests using validity and reliability test. Method of data analysis is a classic assumption test (normality test, multicollinearity, heteroskedastitas test), multiple regression analysis and hypothetical test (F test and t test) with significance level 5%. The test results shows either simultaneously or pasial, indicates that the variable quality of human resources consisting of technical skill, mental attitude, work discipline, work motivation, significant effect on performance. Meanwhile, the technical skill is the dominant variable affecting to the performance of weaving craftsmen small industries in Lamongan.